PENDIDIKAN POLITIK BAGI PENYANDANG DISABILITAS OLEH KPU KOTA PEKANBARU DALAM PEMILU 2024 - Nabil, Daffa Hauzan; ,, Adlin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study examines the role of the Pekanbaru City General Elections Commission (KPU) in providing political education and encouraging the participation of persons with disabilities in the 2024 General Election. In accordance with Law Number 19 of 2011 on the Ratification of the Convention on the Rights of Persons with Disabilities, the state is obligated to guarantee the political rights of persons with disabilities. This research adopts Giesecke’s theory of political education, which includes four aspects: Educational Knowledge (Bildungswissen), Orientational Knowledge (Orientierungswissen), Behavioral Knowledge (Verhaltenswissen) — awareness to act, and Action Knowledge (Aktionswissen). A qualitative approach was used, with data collection techniques including interviews and observations. The findings show that the Pekanbaru City KPU has implemented various accessible election outreach programs to provide fundamental understanding (Bildungswissen) and has provided disability-friendly polling stations to support comprehension of the political system (Orientierungswissen). Training for election officers reflects the development of participatory awareness (Verhaltenswissen). However, the aspect of Aktionswissen remains constrained due to budget limitations and low public awareness. This study highlights the importance of collaboration between the KPU, disability organizations, and the broader community to achieve a more inclusive and democratic election process for all groups, including persons with disabilities. Keywords: General Elections Commission (KPU), Political Education, Persons with Disabilities, Electoral Participation, Pekanbaru City, Bildungswissen, Orientierungswissen, Verhaltenswissen, Aktionswissen.